In vitro and in vivo leishmanicidal and trypanocidal activities of isoflavans from Tabebuia chrysantha (Jacq.) G. Nicholson timber by-products (2025)
ABSTRACT: Cutaneous Leishmaniasis and Chagas disease are neglected tropical diseases that affect millions worldwide. Despite the high morbidity associated with these infections, current treatments are often highly toxic and are showing diminishing efficacy. Thus, new therapeutic options are urgently needed. In this study, bio-guided as says were conducted on the sawdust of Tabebuia chrysantha ("guayacan") to identify promising bioactive com pounds. The ethanolic crude extract, five chromatography fractions, pure isoflavans sativan and vestitol, and a mixture were evaluated in vitro against Leishmania braziliensis and Trypanosoma cruzi. High leishmanicidal and trypanocidal activities were observed in the crude extract, fraction F2 (rich in sativan and vestitol), and the two pure isoflavans. Given the abundance and ease of obtaining the isoflavan mixture, its therapeutic potential was further evaluated in vivo in hamsters infected with L. braziliensis and mice infected with T. cruzi. Remarkably, topical and intraperitoneal administration of the chromatography fraction achieved a 67% clinical cure in hamsters with L. braziliensis infection and a 75% reduction in parasitemia in T. cruzi-infected mice. While the antiparasitic effects of certain flavonoids have been documented, this study is the first to demonstrate the efficacy of isoflavans in animal models for both diseases. The potential efficacy observed against T. cruzi and L. braziliensis, two pathogens with limited treatment options and a significant drawback of the available treat ments, highlights the therapeutic potential of this combination of sativan and vestitol, which can be derived from timber industry waste, presenting an abundant and accessible source for further development.